Identification And Testing The Effectiveness of Bioactive Compounds in Buni Juice as an Antihypercholesterolemic Agent - Nurcahyani, Nuning; Endang L Widiastuti; Yulianty; Primasari Pertiwi; Dzul F Mumtazah (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Buni fruit (Antidesma bunius (L.) Spreng) is thought to be able to treat hypercholesterolemia, a condition where the concentration of cholesterol in the blood exceeds normal and is the main risk factor for Coronary Heart Disease. Scientific data supporting the efficacy of berry as an antihypercholesterolemic agent has not been widely studied, therefore this study aims to examine the chemical compound content and effectiveness of berry as an antihypercholesterolemic agent. Buni fruit juice was tested phytochemically. This study used a Completely Randomized Design (CRD) with 25 mice divided into 5 groups and 5 replications consisting of Negative Control (standard feed), Positive Control (High Fat Diet Food (HFDF) and simvastatin 0.52 mg), P1, P2, P3 (HFDF 14 days followed by 1 ml of 20%, 25%, 30% buni juice 14 days). The parameters measured were LDL (Low-Density Lipoprotein) levels in the blood, which were analyzed using ANOVA and Duncan's test at a 5% significance level. The results of the study, in the form of phytochemical tests, showed that berry fruit contains bioactive compounds, alkaloids, flavonoids, phenols, and tannins. Administration of berry fruit juice at a concentration of 25% was most effective in reducing LDL (Low-Density Lipoprotein) levels in the blood of hypercholesterolemic mice.. Keywords: Antidesma bunius (L.) Spreng., buni fruit, antihypercholesterol, phytochemical test